Mind the body: an exploration of bodily self-awareness - Vignemont, Frédérique de (Oxford University Press, 2018)
A comprehensive treatment of bodily awareness, exploring questions such as: How do I perceive my body? What makes me feel this specific body is my own? These questions are vividly illustrated with examples of bodily illusions and puzzling bodily disorders, which lead us to question some of our most basic intuitions